2018
DOI: 10.3390/ijerph15010091
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change Risk Perception in Taiwan: Correlation with Individual and Societal Factors

Abstract: This study differentiates the risk perception and influencing factors of climate change along the dimensions of global severity and personal threat. Using the 2013 Taiwan Social Change Survey (TSGS) data (N = 2001) as a representative sample of adults from Taiwan, we investigated the influencing factors of the risk perceptions of climate change in these two dimensions (global severity and personal threat). Logistic regression models were used to examine the correlations of individual factors (gender, age, educ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
51
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 72 publications
6
51
0
1
Order By: Relevance
“…In the US, research has found an interaction between political beliefs, with a positive relationship between climate change knowledge and concern among Democrats but a negative relationship among Republicans [ 37 , 38 ]. In an earlier risk perception survey of the entire adult population of Taiwan, education was generally found to predict concern towards climate change [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the US, research has found an interaction between political beliefs, with a positive relationship between climate change knowledge and concern among Democrats but a negative relationship among Republicans [ 37 , 38 ]. In an earlier risk perception survey of the entire adult population of Taiwan, education was generally found to predict concern towards climate change [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The present study seeks to help answer such questions by summarizing key findings from a broader investigation of attitudes towards climate change in Taiwan. Recent studies in Taiwan suggest that a high degree of concern about climate change exists in the adult population [ 20 ] but that this concern has not translated into high levels of behavioral change [ 21 ]. Taiwan’s policymakers have increasingly turned to education to promote sustainable development, culminating in the Environmental Education Act in 2011 [ 22 ], and Taiwan’s public-school teachers have been shown to have adequate levels of environmental literacy [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many papers that consider subjective experience focus on experience with extreme events or disasters, especially flooding [24,47,48,[52][53][54], but also tropical cyclones, drought, wildfire, and other changes [47,49]. Such differences are non-trivial, as each event carries very different risks, is associated with different economic costs, and affects individuals and communities in very different ways.…”
Section: Heterogeneous Measurement and Conceptualization Of Independementioning
confidence: 99%
“…However, several studies present a different view. For example, Sun and Han [45] demonstrate that religious believers have higher risk perceptions of personal threat from climate change than non-religious people. This means that those individuals who are more religious tend to be less skeptical.…”
Section: Religiositymentioning
confidence: 99%
“…The impact of perception on climate change sometimes surpasses the experience. Using 2013 Taiwan Social Change Survey (TSGS) data (N = 2001), Sun and Han [45]) showed that it is not climate-related disaster experience but climate-related risk awareness that has a significant impact on the perception of global severity or personal impact. Poortinga et al [11] demonstrated that a greater perception of risk is associated with a relative decrease in climate change skepticism.…”
Section: Perceived Risk and Benefitmentioning
confidence: 99%